2020
DOI: 10.1155/2020/8859376
|View full text |Cite
|
Sign up to set email alerts
|

Visible Portion of Anterior Teeth at Rest and Analysis of Different Smile Characteristics in the Saudi Population of the Jeddah Region

Abstract: This cross-sectional study aimed to determine the degree of visibility of maxillary and mandibular anterior teeth at rest in different age groups and to evaluate the smile line, smile arc, and number of maxillary teeth displayed during smiling among the Saudi population visiting King Abdulaziz University Dental Hospital, Jeddah, Saudi Arabia. A total of 157 participants (77 males and 80 females) were included in this study with an age range of 19 to 69 years. All participants had maxillary and mandibular anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Following a previous study [ 34 ], gummy smiles are more prevalent in young women than men. A quarter of young women presented with very high smile line compared to 5% of men.…”
Section: Discussionmentioning
confidence: 74%
“…Following a previous study [ 34 ], gummy smiles are more prevalent in young women than men. A quarter of young women presented with very high smile line compared to 5% of men.…”
Section: Discussionmentioning
confidence: 74%
“…The vertical and horizontal over lap of the teeth are termed as over jet and over bite. They have a close relationship with the degrees of gingival display 9 . Some investigators reported their biometric measurements to be on the higher side of the scale in persons having gummy smiles as compare to those with less - ----------------------------------------------------------------------------------------Received on 05-10-2022 Accepted on 07-01-2023 gingival display.…”
Section: Introductionmentioning
confidence: 87%
“…Neurological control of muscles play role in different smile expression 5,6 . Numerous smile parameters can influence natural smile process such as smile line, teeth display, smile arc, labiodental relation of lip 7,8,9 . Besides these components' other parameters like gingival show, facial and dental midline symmetry has impact on pleasing smile 7,9,10 .…”
Section: Introductionmentioning
confidence: 99%